Optical properties of Peaked Spectrum radio sources. Issue 1 (7th January 2022) - Nascimento, R S; Rodríguez-Ardila, A; Dahmer-Hahn, L; Fonseca-Faria, M A; Riffel, R; Marinello, M; Beuchert, T; Callingham, J R
ABSTRACT: In this work, we study the optical properties of compact radio sources selected from the literature in order to determine the impact of the radio-jet in their circumnuclear environment. Our sample includes 58 Compact Steep Spectrum (CSS) and GigaHertz Peaked Spectrum (GPS) and 14 Megahertz-Peaked spectrum (MPS) radio sources located at z ≤ 1. The radio luminosity ( LR ) of the sample varies between Log L R ∼ 23.2 and 27.7 W Hz −1 . We obtained optical spectra for all sources from SDSS-DR12 and performed a stellar population synthesis using the starlight code. We derived stellar masses (M⋆ ), ages 〈 t ⋆ 〉, star formation rates (SFR), metallicities 〈 Z ⋆ 〉 and internal reddening A V for all young AGNs of our sample. A visual inspection of the SDSS images was made to assign a morphological class for each source. Our results indicate that the sample is dominated by intermediate to old stellar populations and there is no strong correlation between optical and radio properties of these sources. Also, we found that young AGNs can be hosted by elliptical, spiral and interacting galaxies, confirming recent findings. When comparing the optical properties of CSS/GPS and MPS sources, we do not find any significant difference. Finally, the Mid-Infrared WISE colours analysis suggests that the compact radio sources defined as powerful AGNs are, in general, gas-rich systems.